2017
DOI: 10.1186/s13075-017-1361-6
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of rheumatoid pain: experimental systems and insights

Abstract: Severe chronic pain is one of the hallmarks and most debilitating manifestations of inflammatory arthritis. It represents a significant problem in the clinical management of patients with common chronic inflammatory joint conditions such as rheumatoid arthritis, psoriatic arthritis and spondyloarthropathies. The functional links between peripheral inflammatory signals and the establishment of the neuroadaptive mechanisms acting in nociceptors and in the central nervous system in the establishment of chronic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…Although biological disease-modifying anti-rheumatic drugs (DMARDs) have revolutionized disease control and long-term outcomes of RA, substantial numbers of patients still suffer from pain despite low disease activity. The use of biological DMARDs has provided new insights into the unique qualities of pain manifestations independent of inflammation in RA [134]. The blockade of TNF-α improves pain faster than the resolution of inflammation or tissue damage, indicating a direct role for TNF-α in nociceptor sensitization pathways [135].…”
Section: Pain In Clinical Ramentioning
confidence: 99%
See 2 more Smart Citations
“…Although biological disease-modifying anti-rheumatic drugs (DMARDs) have revolutionized disease control and long-term outcomes of RA, substantial numbers of patients still suffer from pain despite low disease activity. The use of biological DMARDs has provided new insights into the unique qualities of pain manifestations independent of inflammation in RA [134]. The blockade of TNF-α improves pain faster than the resolution of inflammation or tissue damage, indicating a direct role for TNF-α in nociceptor sensitization pathways [135].…”
Section: Pain In Clinical Ramentioning
confidence: 99%
“…The K/BxN model exhibits persistent pain with mechanical hypersensitivity, which does not return to baseline levels during disease progression and outlasts inflammation [155]. Table 2 briefly summarizes the pathology and pain behaviors reported in RA models [134,137,[153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]. CIA, collagen-induced arthritis; CAIA, collagen antibody-induced arthritis; AIA, antigen-induced arthritis; TNF-Tg, tumor necrosis factor transgene; IL-1RA-/-, interleukin-1 receptor antagonist knockout; CII, collagen type II; Ab, antibody; mBSA, methylated bovine serum albumin; GPI, glucose-6-phosphateisomerase; hTNF, human tumor necrosis factor; RA, rheumatoid arthritis; d, day; wk, week(s); Cat S, cathepsin S; FKN, fractalkine; TLR-4, toll-like receptor 4; IL-1RI, interleukin-1 receptor type I; pCREB, phospho-CREB.…”
Section: Behavioral Tests To Assess Pain In Ra Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental animal models have been exploited to unravel the pathophysiology of inflammatory arthritis [ 7 12 ]. However, in most of these studies the primary research focus was on disease pathways and immune cells of the synovium rather than extra-articular manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the exogenous tIK protein produced using an insect cell culture expression system has the potential to be used as an arthritis therapy. Considering the disease model, it has been reported that the CAIA model is less dependent on B and T cells than the CIA model [ 28 ], although some reports have indicated that T cells are involved in the development of inflammatory arthritis in the CAIA model [ 29 ]. Therefore, our disease model (CAIA) has limitations in testing the effects of tIK protein, which have been previously reported as the suppression of Th17 cell differentiation and macrophage activation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%